A case of acute obstructive pyelonephritis due to bleeding from a renal pelvis cancer rescued with laparoscopic nephrectomy - Masato Yanagi; Ken Takahashi; Yuta Kikuchi; Takuya Takahashi; Hideaki Iwata; Hiro Izuta; Shuichi Osawa; Taiji Nishimura; Yukihiro Kondo (IJU Case Reports, 2025)
Introduction We encountered a case of acute obstructive pyelonephritis caused by bleeding from a renal pelvis cancer that was successfully treated by laparoscopic nephrectomy. Case presentation An 88‐year‐old woman with fever of 40.2°C and right back pain associated with hematuria due to a right renal pelvic tumor. Computed tomography showed a blood clot filling the right renal pelvis and ureter. She was diagnosed with severe obstructive pyelonephritis due to undrainable blood clots. Nephrectomy was performed to control the infection. Although the perirenal area was easy bleeding, nephrectomy was completed and the patient's condition improved. Conclusion Renal pelvis carcinomas with hemorrhage requiring blood transfusion should be treated with radical nephroureterectomy as early as possible.